2024
DOI: 10.3390/antiox13020218
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Systemic Antioxidative Effects of Intermittent Theta Burst Stimulation beyond Neurodegeneration: Implications in Therapy in 6-Hydroxydopamine Model of Parkinson’s Disease

Milica Zeljkovic Jovanovic,
Jelena Stanojevic,
Ivana Stevanovic
et al.

Abstract: Parkinson’s disease (PD) is manifested by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and caudoputamen (Cp), leading to the development of motor and non-motor symptoms. The contribution of oxidative stress to the development and progression of PD is increasingly recognized. Experimental models show that strengthening antioxidant defenses and reducing pro-oxidant status may have beneficial effects on disease progression. In this study, the neuroprotective potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Antioxidants have neuroprotective properties and may help to prevent or delay the onset of neurodegenerative diseases by reducing oxidative stress in the brain [40]. In this Special Issue, Jovanovic et al [41] reported a complex interaction between ROS and antioxidants in a model of Parkinson's disease (PD). This study demonstrated that intermittent theta burst stimulation (iTBS) in a rat model of PD significantly bolsters antioxidative capacity and acts as a neuroprotective mechanism in specific brain regions associated with PD.…”
Section: Antioxidants and Brain Healthmentioning
confidence: 99%
“…Antioxidants have neuroprotective properties and may help to prevent or delay the onset of neurodegenerative diseases by reducing oxidative stress in the brain [40]. In this Special Issue, Jovanovic et al [41] reported a complex interaction between ROS and antioxidants in a model of Parkinson's disease (PD). This study demonstrated that intermittent theta burst stimulation (iTBS) in a rat model of PD significantly bolsters antioxidative capacity and acts as a neuroprotective mechanism in specific brain regions associated with PD.…”
Section: Antioxidants and Brain Healthmentioning
confidence: 99%